Towards resilience: Transcriptional insights on flavonoid biosynthesis during peanut seed maturation phases - Gustavo Roberto Fonseca de Oliveira; Liam Walker; Rômulo Pedro Macêdo Lima; Thiago Barbosa Batista; Clíssia Barboza Mastrangelo; Edvaldo Aparecido Amaral da Silva (PLoS ONE, 2025)
Flavonoids are secondary metabolites widely studied as a metabolic protector against several stressors in plants, yet they are understudied in the events of peanut seed development. Substantial advances in the understanding of peanut seed maturation have been made in recent years, however, the role of flavonoids in this process is unclear. Here, the fundamental question asked was: are flavonoids involved in peanut seed maturation phases? This study investigates whether the main transcripts associated with the flavonoid pathway, such as anthocyanins, are biologically linked to the physiological quality components of peanut seeds during development. For this purpose, peanut seeds classified into five stages (R5, R6, R7, R8 and R9) were used for the evaluation of quality attributes, such as desiccation tolerance, vigor and longevity parameters, and for RNA sequencing (RNA-seq). Interestingly, anthocyanins accumulated more in the beginning of the seed filling phase, coinciding with the expression upregulation in RNA-seq and quantitative PCR of key genes in its pathway, such as AhCHS (0FI6RG), AhCHI (VJQ7J1), AhFLS (4Y1607), AhLDOX (AQ6B1J) and AhANR (IK60LM). Additionally, we found that AhMYB12 (PR7AYB) and AhMYB308 (TG6F30) exhibited increased expression at the early stages (R5 and R6) and decreased at the later ones (R7, R8 and R9). The AhCHS expression acts in synergy with well-known seed maturation regulators, such as the ABA response (e.g., ABI5 and ABI3). The involvement of flavonoid biosynthesis in peanut seed development is suggested here as a contributor to its resilience during the acquisition of physiological quality attributes, highlighting the molecular aspects associated with survival in the dry state.